Plasma α‐L‐fucosidase‐1 in patients with Sjögren's syndrome and other rheumatic disorders. (16th August 2019) - Endreffy, Ildikó; Bjørklund, Geir; Bartha, Attila; Chirumbolo, Salvatore; Dadar, Maryam; Fényi, Ágnes
Abstract: Background: Human α‐fucosidase (EC 3.2.1.51) is a hydrolase the importance of which has been increasing in the latest years. However, data about its plasma level in children with autoimmune disorders, particularly Sjögren's syndrome (SS), are lacking. In this study, the plasma activity of L‐α‐fucosidase‐1 (α‐L‐FUCA‐1) was assayed in hospitalized children and adults and its association with SS and other rheumatic disorders further evaluated. Methods: In total 73 Hungarian hospitalized patients, 32 children (2.5‐10 years) and 41 adults (32‐68 years), were enrolled in the study and underwent plasma assay of α‐L‐FUCA1 activity. Linear regression, Durbin‐Watson (DW), and Pearson tests were evaluated to investigate the relationship between α‐L‐FUCA‐1 plasma levels and autoimmune manifestations. Results: α‐L‐FUCA‐1 correlated with SS both in children (2‐sided t test, P  = 0.0023) and in adults (2‐sided t test, P  = 0.00035). Linear regressions showed that in other rheumatic disorders, α‐L‐FUCA1 did not show any differential distribution related to the particular pathology ( r  = 0.2042, P  = 0.1531, DW test = 2.2139 positive), while this trend was radically opposite for patients with SS ( r  = 0.1462, P  = 0.0032, DW test = 1.3664, negative). Conclusions: Alterations in plasma level of α‐L‐FUCA‐1 were significantly associated with SS. This preliminary result should encourage further research on α‐L‐FUCA‐1 as a possible differential serological marker of SS.